2021
DOI: 10.14309/ajg.0000000000001347
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Effect of Statin on Hepatocellular Carcinoma in Patients With Nonalcoholic Steatohepatitis Cirrhosis

Abstract: INTRODUCTION: To estimate the annual incidence of hepatocellular carcinoma (HCC) in patients with nonalcoholic steatohepatitis (NASH) with advanced liver fibrosis, to determine the risk factors for the development of HCC, and to evaluate the chemoprotective effect of statin use stratified by fibrosis stage. METHODS: We conducted a retrospective study at 2 US tertiary academic centers, including patients with NASH-related advanced liver fibrosis (bridgin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Our findings not only add information on patients with CKD and ESRD but also extend previous meta-analyses findings linking statin therapy to a reduced risk of HCC [20][21][22], in patients with diabetes, cirrhosis or antiviral therapy [20] and patients with non-alcoholic steatohepatitis (NASH) [23]. An earlier case-control research reported that the prolonged use of statins was associated with increased risk of colorectal cancer, bladder cancer and lung cancer [24].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our findings not only add information on patients with CKD and ESRD but also extend previous meta-analyses findings linking statin therapy to a reduced risk of HCC [20][21][22], in patients with diabetes, cirrhosis or antiviral therapy [20] and patients with non-alcoholic steatohepatitis (NASH) [23]. An earlier case-control research reported that the prolonged use of statins was associated with increased risk of colorectal cancer, bladder cancer and lung cancer [24].…”
Section: Discussionsupporting
confidence: 81%
“…An earlier review study also failed to find clinical benefits of statin therapy for cancer patients [17]. However, prolific clinical studies and basic laboratory studies have reported evidence supporting the anti-cancer effects of statins [13,18,20,23,25].…”
Section: Discussionmentioning
confidence: 99%
“…5B). The second example is use of lipophilic statins such as atorvastatin and simvastatin, which is associated with reduced HCC incidence in NAFLD patient cohorts (HR, 0.36) ( 44 ). Prevalence of high-risk PLS-NAFLD in lipophilic statin users was threefold lower compared to nonstatin users (conditional OR, 0.33; 95% CI, 0.16 to 0.68) in severely obese patients, which is again comparable to the magnitude of reduction in HCC incidence (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated the reduction of HCC in NASH patients with advanced liver fibrosis and cirrhosis. The relevance of this retrospective study was found to be an association statin and a lower risk of developing HCC (23.6%) [87]. As the most interesting data for this review, it is important to mention that statin use also decreased the risk of NAFLD and liver fibrosis [88].…”
Section: Could Cholesterol Inhibitors Be Used As Immunotherapy?mentioning
confidence: 79%